Teknologi Keuangan dan Inklusi Keuangan UMKM: Peran Moderasi Infrastruktur Digital di Wilayah Kepulauan - Rumtutuly, Hansen Hein (Jurnal Ekonomi dan Kewirausahaan West Science, 2026)
Financial inclusion remains a major challenge for MSMEs, particularly in island regions facing limited access to formal financial institutions, disparities in digital infrastructure, and high transaction costs. This study aims to analyze the effect of financial technology (fintech) on MSMEs’ financial inclusion while also examining the moderating role of digital infrastructure in the context of the Maluku island economy. The study population comprised MSMEs operating in the Maluku islands with access to digital devices, with a total sample of 250 MSMEs selected using purposive sampling based on the criteria of being active for at least one year and having experience with fintech services. Data were collected through structured questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to simultaneously test direct causal relationships and moderation effects. The results indicate that fintech has a positive and significant effect on MSMEs’ financial inclusion, and digital infrastructure strengthens this effect by enhancing access, usage, and quality of financial services. The novelty of this study lies in integrating the Technology Acceptance Model (TAM) with digital infrastructure as a moderating variable to explain fintech adoption in island regions, thus addressing the research gap related to challenging geographical contexts. Practically, these findings provide important implications for policymakers and fintech developers, highlighting that strengthening digital infrastructure should be a strategic priority to maximize fintech benefits and expand MSMEs’ financial inclusion in remote areas.